2019
DOI: 10.5539/ijef.v11n3p127
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Corporate Financing Decisions on Firm Value in Bursa Malaysia

Abstract: The primary objective of shareholders and financial managers is generally stated to be the maximization of shareholders' wealth by increasing the firm value. This research was undertaken to investigate the effect of corporate financing decisions on firm value. The research has been carried out using the panel data procedure for a sample of 256 firms from 9 sectors listed on Bursa Malaysia during the period 2000-2015. The study uses Tobin's Q representing firm value for the dependent variable. The corporate fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
6
0
5
Order By: Relevance
“…Ghaleb et al (2020) also use ownership concentration with a limit of 20 percent or more to test the impact of family ownership concentration on real earning management in manufacturing companies listed on Bursa Malaysia. Second, debt policy is debt ratio (TDTA), measured by the ratio of total debt to the total asset (Chaleeda et al, 2019;Lima & Hossain, 2018;Sulong & Nor, 2010).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Ghaleb et al (2020) also use ownership concentration with a limit of 20 percent or more to test the impact of family ownership concentration on real earning management in manufacturing companies listed on Bursa Malaysia. Second, debt policy is debt ratio (TDTA), measured by the ratio of total debt to the total asset (Chaleeda et al, 2019;Lima & Hossain, 2018;Sulong & Nor, 2010).…”
Section: Independent Variablesmentioning
confidence: 99%
“…To the best of our knowledge, Malaysia lacks studies that examined the direct influence of debt on the growth of large public listed companies, especially after the global financial crisis in order to understand the ability of bond market in providing financing resources to Malaysian firms. In Malaysia, Chaleeda et al (2019) showed that corporate debt has a positive relationship with firm value. They argued that it was debt financing which assisted in mitigating the agency cost which led to improved firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…expansion, crisis, recession and recovery, are important as they encompass the whole businesses circle during which, firms used debt for growth. Thirdly, unlike Chaleeda, Islam, Tunku Ahmad, & Mosa Ghazalat (2019), Ayaz et al (2021) and Hasan et al (2021), which examined the indirect impact of debt to firm's growth through the firm performance perspective, this research investigated this relationship in a direct way, i.e. looking at the direct effect of firm's debt to sales and asset growth…”
Section: Introductionmentioning
confidence: 99%
“…For its part, the literature on financial behavior is large but, paradoxically not conclusive. There are mainly three financial decisions that can influence the firm value which are investment decisions, financing decisions, and dividend decisions (Chaleeda, Islam, Ahmad & Ghazalat, 2019). Besides, financial decision-making is a priority concern for any form of business.…”
Section: Introductionmentioning
confidence: 99%